The Protective Role of E-64d in Hippocampal Excitotoxic Neuronal Injury Induced by Glutamate in HT22 Hippocampal Neuronal Cells - RuiJin Xie; TianXiao Li; XinYu Qiao; HuiYa Mei; GuoQin Hu; LongFei Li; Chenyu Sun; Ce Cheng; Yin Cui; Ni Hong; Yueying Liu (Neural Plasticity)
Epilepsy is the most common childhood neurologic disorder. Status epilepticus (SE), which refers to continuous epileptic seizures, occurs more frequently in children than in adults, and approximately 40–50% of all cases occur in children under 2 years of age. Conventional antiepileptic drugs currently used in clinical practice have a number of adverse side effects. Drug-resistant epilepsy (DRE) can progressively develop in children with persistent SE, necessitating the development of novel therapeutic drugs. During SE, the persistent activation of neurons leads to decreased glutamate clearance with corresponding glutamate accumulation in the synaptic extracellular space, increasing the chance of neuronal excitotoxicity. Our previous study demonstrated that after developmental seizures in rats, E-64d exerts a neuroprotective effect on the seizure-induced brain damage by modulating lipid metabolism enzymes, especially ApoE and ApoJ/clusterin. In this study, we investigated the impact and mechanisms of E-64d administration on neuronal excitotoxicity. To test our hypothesis that E-64d confers neuroprotective effects by regulating autophagy and mitochondrial pathway activity, we simulated neuronal excitotoxicity in vitro using an immortalized hippocampal neuron cell line (HT22). We found that E-64d improved cell viability while reducing oxidative stress and neuronal apoptosis. In addition, E-64d treatment regulated mitochondrial pathway activity and inhibited chaperone-mediated autophagy in HT22 cells. Our findings indicate that E-64d may alleviate glutamate-induced damage via regulation of mitochondrial fission and apoptosis, as well as inhibition of chaperone-mediated autophagy. Thus, E-64d may be a promising therapeutic treatment for hippocampal injury associated with SE.